2019
DOI: 10.14444/6047
|View full text |Cite
|
Sign up to set email alerts
|

Direct Fixation of C1 Jefferson Fracture Using C1 Lateral Mass Screws: A Case Report

Abstract: Background: Jefferson fractures are classically described as burst fractures of C1. Traditional surgical treatment of these unstable fractures is either occipito-cervical or posterior C1-C2 fusion, resulting in a significant loss of range of cervical neck movement. This case report discusses the fixation of a Jefferson fracture using C1 lateral mass screws to achieve surgical stabilization while preserving the range of movement. We aim to add to the body of evidence supporting this fixation method. Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…Surgical options include C1–C2 fixation, with occipitocervical fusion reserved for those with the most complex findings. Although there have been reports of direct fixation of C1 only,[ 4 ] pseudoarthrosis is not a viable option in our opinion. Our case of an unstable Type III fracture involving both anterior, posterior, and lateral mass is cited to have a 33.3% prevalence of nonunion with either operative and nonoperative management.…”
Section: Discussionmentioning
confidence: 86%
“…Surgical options include C1–C2 fixation, with occipitocervical fusion reserved for those with the most complex findings. Although there have been reports of direct fixation of C1 only,[ 4 ] pseudoarthrosis is not a viable option in our opinion. Our case of an unstable Type III fracture involving both anterior, posterior, and lateral mass is cited to have a 33.3% prevalence of nonunion with either operative and nonoperative management.…”
Section: Discussionmentioning
confidence: 86%
“…The clinical implication of this report was that the treatment options for the Jefferson fracture vary depending on the presence of other cervical injuries related to the main injury. [ 1 , 14 , 22 , 23 ] For a nonoperative treatment, the use of a halo-thoracic brace, rigid collar, or sterno-occipitomandibular immobilization is effective for a stable fracture. [ 1 , 2 , 6 , 14 ] Meanwhile, operative treatment is used for more unstable and complex fracture cases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 14 , 22 , 23 ] For a nonoperative treatment, the use of a halo-thoracic brace, rigid collar, or sterno-occipitomandibular immobilization is effective for a stable fracture. [ 1 , 2 , 6 , 14 ] Meanwhile, operative treatment is used for more unstable and complex fracture cases [ 22 ]. More importantly, this report showed that sport injury can cause cervical injury, therefore complete neurologic examination should be performed cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…ORIF is an emerging surgical technique in recent years, and scholars have tried a variety of surgical approaches and methods. Currently, the surgical methods include anterior transoral screws and plate reduction and fixation [ 21 , 22 ], posterior screws and plate or PSR reduction and fixation [ 23 , 24 ], as well as anterior and posterior combined approach reduction and fixation [ 25 ]. Among these, PSR fixation is the most common one, typically involving the placement of polyaxial pedicle screws in the lateral masses of the atlas, connected by a titanium rod, and then repositioned under pressure.…”
Section: Introductionmentioning
confidence: 99%